1981
DOI: 10.1302/0301-620x.63b1.7204474
|View full text |Cite
|
Sign up to set email alerts
|

Exercise testing after the Chiari pelvic osteotomy

Abstract: The work capacity of 26 women after a Chiari pelvic osteotomy for symptomatic unilateral subluxation of the hip was assessed using two simple exercise tests: the maximal walking speed during a 12-minute test and the time taken to climb stairs. A significant linear decline in walking speed occurred with increasing age, despite the operation, and only one patient over the age of 25 years was able to walk at a normal rate. Compared to the results in a control group of women of similar age the stair climbing time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Long-term review inevitably shows a decline in the relief from pain, with an associated decrease in function. 16,17 As shown in the Kaplan-Meier survival graph (Fig. 2) there are some relatively early revisions, although the survival at 20 years was almost 95%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Long-term review inevitably shows a decline in the relief from pain, with an associated decrease in function. 16,17 As shown in the Kaplan-Meier survival graph (Fig. 2) there are some relatively early revisions, although the survival at 20 years was almost 95%.…”
Section: Discussionmentioning
confidence: 94%
“…Cover of at least 80% should be achieved, but there is no merit in excessive displacement producing greater than 100% cover since union of the osteotomy may be impaired and a limp may persist. 17 Remod-elling of the pelvis does not reduce support of the head although associated coxa valga may require correction. 3,18 The alteration in architecture of the pelvic wall largely affects the medial pillar and the brim, producing remodelling which may not be seen after a Salter osteotomy of the mature pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…- The 1MSCT : The patient is invited to walk up and down stairs (one step at a time) for 1 min, the score being the total number of steps climbed [6].…”
Section: Methodsmentioning
confidence: 99%
“…Many performance tests are currently being used by clinicians, especially in rehabilitation centers. Among these tests, the 6-min walk test (6MWT) [4], the Steep Ramp Test (SRT) [5], the 1-Minute Stair Climbing Test (1MSCT) [6], the Sit-To-Stand test (STS) [7], the Jamar dynamometer test (JAM) [8] and the lumbar protocol of the Progressive Isoinertial Lifting Evaluation (PILE) [9] are widely used in patients with musculoskeletal, neurological, cardiac or pulmonary disease. These tests are easy to administer and do not require expensive devices.…”
Section: Introductionmentioning
confidence: 99%
“…Mannor et al [26] recorded a revision rate of 20% 2-19 years after Chiari osteotomy. Long-term review inevitably shows a decline in the relief from pain, with an associated decrease in function [27,28]. In a long-term review, Macnicol et al [21] showed that although there are some relatively early revisions, the survival at 20 years is almost 95%.…”
Section: Chiari Pelvic Osteotomy In Developmental Dysplasia Of the Hi...mentioning
confidence: 99%